Rancang Bangun Sistem Informasi Sekolah Berbasis Android dengan Metode Waterfall Pada TKIT Husnul Khotmah - Ari Wibowo; Firman Noor Hasan (Universitas Pancasila, 2026)
TKIT Husnul Khotimah Cibitung is still facing challenges in managing school information because student registration, tuition fee payments, announcement delivery, schedules, teacher data, student data, and grade processing have not yet been digitally integrated. This research aims to design and build an Android-based school information system to facilitate communication between operators, teachers, and parents. The research method uses the Software Development Life Cycle Waterfall model, which consists of requirements analysis, design, implementation, testing, and evaluation. The system is designed using UML and DFD, implemented with Java on the Android platform, and supported by a MySQL/phpMyAdmin database. Testing is conducted using Blackbox Testing on the operator web module, teacher web module, and parent student application, followed by an ease of use evaluation thru a questionnaire. The research results show that the system is capable of providing registration services, online tuition fee payments, grade management, announcements, schedules, lessons, teacher data, and student data. User evaluations yielded scores of 85% for operators, 92.8% for teachers, and 92% for parents. This system contributes to the digitalization of integrated and user-friendly kindergarten information services.